Analysis of the Flow Pulsation of Straight Conjugated Internal Gear Pump - Zhang Hui; Wang Zhonghou (Jixie chuandong)
Based on flow pulsation formula of the straight internal gear pump,the straight conjugate internal gear pump is studied,the instantaneous flow rate formula is derived and the reliability of the formula is verified by experiment.The maximum and minimum of the instantaneous flow are obtained after the analysis of engagement characteristic in detail and the formula for the flow pulsation is derived.The influence of factors such as dedendum coefficient and half profile angle on the pulsation are analyzed,the impact curves are plotted in MATLAB and the optional dedendum coefficient is obtained through the curves.It can help improve the transmission stability of the pump.